L’Insomnie d’Edmundo O'Gorman : Récit, preuve et historiographie - Pablo Avilés Flores (Nuevo mundo - Mundos Nuevos, 2012)
At an early age, O’Gorman developed a critique of Ranke’s work. Influenced by Heidegger, he began the task of interpreting the past by taking the human being into account. His methodology did not look at the evidence, documents and testimonies as the acknowledgement of historical events, but as keys elements to the interpretation of their purpose.